Detection of malarial DNA in blood donors – evidence of persistent infection. Issue 2 (21st March 2014) - Kitchen, A. D.; Chiodini, P. L.; Tossell, J.
<x xml:space="preserve">Abstract</x> Background and Objectives The English transfusion service has screened donations from malaria‐risk donors for malarial antibodies for over 10 years. The donor population includes migrants from many malaria‐endemic countries and, from our experiences with post‐transfusion malaria, some of these may remain parasitaemic and need clinical review. Materials and Methods Malarial antibody screen‐reactive donations with serological evidence of malaria identified by the reference laboratory were further investigated for the presence of malarial DNA. Results Malarial DNA was found in 14 of 1955 samples investigated; three P. falciparum, five P. vivax, three P. ovale, two P. malariae and one dual parasitaemia P. falciparum/P. malariae. All of these were donors whose malaria risk was residency rather than travel. Conclusion Malarial parasitaemia in healthy donors occurs, and donor malaria‐risk strategies must take into account the possibility of such donors presenting. Countries not utilizing malarial antibody screening should consider carefully the collection of donations from donors previously resident in endemic countries; temporary deferral is insufficient.